The changing landscape in nephrology education in India - Vali, P. S.; Parikh, Namrata; Mohan, Krithika; Anandh, Urmila (Frontiers in Nephrology, 2023)
Digital tools have revolutionised education in nephrology in India. All forms of in person learning is going online. Social media is promoting multi-directional education methods. e-learning is better suited to keep up with the rapid pace of new knowledge generation and dissemination. Several scientific organizations in India (Women In Nephrology-India, Indian Society of Organ Transplantation etc,), have dedicated social media teams to cover their conferences on various platforms. #NephJC, a twitter- based journal club, has even had first authors join their chats allowing questions and comments directed to them from participants. Besides Twitter, Facebook live allows audiences to interact with the educator and has great potential to target audiences especially patients and caregivers. Also ,Instagram and Linkedin allow two- way conversations although not in real time. Digital education has been used in creating awareness about chronic kidney disease in the general population and improving adherence to treatment in patients with kidney disease. Several organizations such as the Kidney Warrior foundation which is an India-based network of kidney patients, caregivers, healthcare professionals, and social workers use social media widely to advocate for policies that improve access to quality health care for patients with kidney disease. All technology comes with some drawbacks. Digital tools have their own pitfalls- 1.Accessibility and connectivity 2. Authenticity of scientific information. 3. Social media noise 4. Patient privacy.These can be addressed by avoiding social media overload and adopting peer review processes. It is always advisable to seek written consent from patients whenever patient data is posted online.